Data for "Impact of Surface Adsorbates and Dimensionality on Templating of Halide Perovskites" - Fransson, Erik; Wiktor, Julia; Erhart, Paul (Chalmers University of Technology, 2024)
This record contains databases with data from density functional theory calculations used for training of a neuroevolution potential (NEP) for 2D halide perovskites.
Keywords: Physical Sciences; Fysik